Rapid screening technique for assessing resistance to Meloidogyne spp. in cassava - Coyne, Danny L.; Kagoda, A.; Mbiru, E. (2012)
Root-knot nematodes (Meloidogyne spp.) are a particularly damaging group of pests on a wide range of crops and the predominant plant-parasitic nematode occurring on cassava (Manihot esculenta). Screening for resistance against these nematodes would be prudent to minimize yield loss and the high costs of alternative control measures. However, existing screening methods using pots are laborious and time consuming. This study was initiated with the major objective of establishing a reproducible and rapid screening protocol for cassava against Meloidogyne spp. Three experiments were established using four node cuttings of cv. Nase 4 (SS4) planted in vertically hanging 20 cm diameter, sawdust filled polythene tubing. The study evaluated different irrigation methods, plant spacing and position along the tube following inoculation with Meloidogyne spp. using different methods and densities. The technique was refined with progression of the study towards determining a suitable protocol. Individual inoculation of cuttings was superior to drenching the sawdust with a nematode suspension. Irrigating the tubes through a plastic pipe installed down the centre resulted in higher and more uniform galling and Meloidogyne spp. densities in roots than without pipes. Plant spacing at 30 × 30 cm and 25 × 25 cm resulted in better plant growth despite inoculation with Meloidogyne spp. than narrow spacing (20 × 20 cm). Inoculation levels (1000, 500 and 250 Meloidogyne spp.) caused no measurable difference to plant growth or nematode variables although 1000 Meloidogyne spp. eggs appears the minimum inoculation level necessary to effect a reduction in plant growth components. The use of a tube for screening against Meloidogyne spp. is therefore proposed as a space and resource saving technique suitable for cassava stems and perhaps other plants too.